ChemInform Abstract: An Efficient Synthesis of 2, 4, 7‐Trisubstituted Pyrimido[1, 2‐a][1, 3, 5]triazin‐6‐ones. Issue 43 (October 2015) - Sachdeva, Nikhil; Dolzhenko, Anton V.; Lim, Seow Joo; Ong, Wee Ling; Chui, Wai Keung
Abstract Title compounds are obtained by reaction of guanidine derivatives with alkyl and aryl aldehydes.